Organophosphate ester contamination in long-term plasticulture soils: Co-occurrence of tri/di-OPEs, influence factors, source Attribution, and environmental risks - Yangyang Liu; Yuting Ren; Huijie Dang; Mengfei Liu; Ke Hu; Ang Zhao; Wei Liu; Yuxia Yang; Chao Wei; Jianzhong Xu; Mei Wang (Emerging Contaminants, 2025)
This study focused on the pollution characteristics, influencing factors, and source apportionment of organophosphate triesters (tri-OPEs) and diesters (di-OPEs) in the plastic greenhouses soils with cultivation periods ranging from 6 to 32 years. The concentrations of Σ13tri-OPEs and Σ5di-OPEs in soil samples ranged from 39.60 to 730.52 ng/g dw and 2.25–6.94 ng/g dw, respectively. Tris (chloroethyl) phosphate was the predominant tri-OPE, while dibutyl phosphate was the most abundant di-OPE. The levels of OPEs pollution increased with the age of mulch film, highlighting the impact of the duration of mulch film usage on OPE accumulation. The type of fertilizer significantly impacted OPE levels. Soil samples treated with compound fertilizers showed the highest concentration of tri-OPEs, reaching up to 205.32 ng/g dry weight. In contrast, the highest concentration of di-OPEs was found in soil samples treated with water-soluble fertilizers, with a peak of 3.89 ng/g dry weight. Total organic carbon, pH, total nitrogen, and total phosphorus had minimal effect on OPEs levels. According to the Positive Matrix Factorization Model, the primary sources of OPEs included the use of pesticides, food packaging materials, and small-scale machinery (48.39 %), water and reclaimed water irrigation (17.68 %), the utilization of agricultural films (17.39 %), and atmospheric deposition and degradation processes (16.54 %). Compared to the moderate risks associated with compounds such as tri-2-ethyl phosphate, 2-ethylhexyl diphenyl phosphate, and tris(1-chloro-2-propyl) phosphate, tris(chloroethyl) phosphate exhibited a higher risk level in soil samples. This study offers insights into the potential risks linked to OPE contamination in agricultural soils.